2021
DOI: 10.1155/2021/9538647
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of Propellers for Multirotor Unmanned Aerial Vehicles: Measurement, Analysis, and Experiment

Abstract: Analyzing the propeller aerodynamic performance is of vital importance for research and improvement of unmanned aerial vehicles. This paper presents the design requirements for a propeller for rotorcraft unmanned aerial vehicles and an analysis of a model for calculating propeller aerodynamic performance. Based on blade element momentum theory, the aerodynamic force of a blade element is analyzed and used. The symmetric airfoil NACA 0012 is used as an example to verify the validity of the model. An experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Zhu et al calculated the thrust, drag and power of the propeller and analyzed its aerodynamic performance based on the theory of blade element momentum. A calculation model for blade parameter selection of multirotor UAV is established, and the feasibility and rationality of the model are verified by taking the symmetrical airfoil NACA 0012 as an example (Zhu et al , 2021). Jiao et al designed the main parameters of the propeller, such as pitch angle, chord length, diameter and rotational speed, based on the eddy current theory, and optimized the designed propeller using NSGA-II genetic algorithm (Jiao et al , 2017; Park et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al calculated the thrust, drag and power of the propeller and analyzed its aerodynamic performance based on the theory of blade element momentum. A calculation model for blade parameter selection of multirotor UAV is established, and the feasibility and rationality of the model are verified by taking the symmetrical airfoil NACA 0012 as an example (Zhu et al , 2021). Jiao et al designed the main parameters of the propeller, such as pitch angle, chord length, diameter and rotational speed, based on the eddy current theory, and optimized the designed propeller using NSGA-II genetic algorithm (Jiao et al , 2017; Park et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They found that performance parameters such as thrust, drag, and power are based on blade element theory. Their research results indicate that both thrust and torque increase with increasing propeller rotational speed, RPM, and pitch coefficient [12]. Dogru et al utilized a static pressure measurement system to evaluate the thrust of a ducted fan location on the ground effect [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For plant protection applications, the UAVs typically take-off and land vertically in the tea garden. The high-speed downward swirling airflow, and water and fertilizer spraying devices are able to turn the tea leaves, allowing for the even spraying of the front and back of the leaves (Lan et al, 2010;Kose and Oktay, 2020;Qin et al, 2021;Zhan et al, 2021;Zhu et al, 2021;Şahin et al, 2022). UAV multi-tea field scheduling route planning is an important component of the precision planting and protection of tea fields.…”
Section: Introductionmentioning
confidence: 99%